1954
DOI: 10.1103/physrev.93.1286
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Cross Sections at Low Energies

Abstract: The note is concerned with estimates of the accuracy of the one-term formula for the energy dependence of the reaction cross section for charged particles. The second term in an expansion of the cross section in powers of the energy is worked out for a one-body model. Comparison with data of Sawyer and Phillips on the bombardment of Li and Be with protons and deuterons shows that the deviations from the one-term formula are of the correct order of magnitude to be accounted for by the second term. This term was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1955
1955
1964
1964

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Looking at the experimental results from three groups [2][3][4] in the energy region of about 8 to 100 k ev (center of mass), Brennan [5] has indicated that the d ata might suggest an increase in B of eq (1) with energy. Brennan calculated the D-D reaction cross section using a low energy approximation [6] to the small absorption method of Ostrofsky, Breit, and John son [7]. In this present paper, the energy dependence of the reaction cross section h as been studied under various assumptions suggested by this previous work.…”
Section: (In= (A /E) Exp (-Be-i)mentioning
confidence: 91%
See 1 more Smart Citation
“…Looking at the experimental results from three groups [2][3][4] in the energy region of about 8 to 100 k ev (center of mass), Brennan [5] has indicated that the d ata might suggest an increase in B of eq (1) with energy. Brennan calculated the D-D reaction cross section using a low energy approximation [6] to the small absorption method of Ostrofsky, Breit, and John son [7]. In this present paper, the energy dependence of the reaction cross section h as been studied under various assumptions suggested by this previous work.…”
Section: (In= (A /E) Exp (-Be-i)mentioning
confidence: 91%
“…Johnson and Jones [6] have shown that in the low energy limit the approach cross sections of the OB.J method are given by where r} =e 2 /hv cx. E -!…”
Section: Small Absorption Approximation At Very Low Energiesmentioning
confidence: 99%